(untitled) (Itinera, 2017)
Although it plunges the viewer into a more or less familiar world, contemporary theatre at times employs a dramatic primer that, by just preceding the performance itself, plays a crucial role in the process of resensitization of the audience that is present at such an event. This process can be theorized through the notion of the experience where the theatrical event is transformed, and through the liminal quality of the introduction that precedes it. With the help of two remarkable Québécois theatre performances – Les Troyennes d’Euripide and Ascension d’Olivier Choinière – this article will investigate how the dramatic primer allows for the activation of the viewer’s senses by reconnecting them with a moving, touching, dynamic, feeling body, in order to broaden his openness beyond the everyday reality.